Emotional intelligence : the key to future successful corporate leadership? - Dulewicz, Victor (2000)
Looks at why Emotional Intelligence (EI) appears to be important for leaders of companies. Describes two recent studies, including the development of the first psychometric test to measure EI. Presents a model to explain how the various elements fit together and discusses the implications for leadership. Produces evidence from a national study of UK Boards which supports the proposition that EI is required at the very top level within companies.